2019
DOI: 10.7150/thno.33395
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock Gene Bmal1 Controls Intestinal Exporter MRP2 and Drug Disposition

Abstract: The intestinal exporter MRP2 plays an important role in disposition and elimination of a wide range of drugs. Here, we aimed to clarify the impact of circadian clock on intestinal MRP2, and to determine the molecular mechanisms for generation of diurnal MRP2 expression. Methods : The regulatory effects of Bmal1 on intestinal MRP2 expression were assessed using intestine-specific Bmal1 knockout ( Bmal1 iKO ) mice and colon cancer cells. The relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 48 publications
(57 reference statements)
3
49
0
Order By: Relevance
“…In addition to gender, microbiome may be another influencing factor to inter-subject variations of circadian pattern in Cyp3a11 40 . We show Bmal1 controls circadian expressions of Cyp3a11 in the present study and of intestinal Mrp2 in our recent study 41 . BMAL1 has potential to regulate other key metabolic enzymes and transporters such as UGT1A1, CES2 and P-gp 42 .…”
Section: Discussionsupporting
confidence: 80%
“…In addition to gender, microbiome may be another influencing factor to inter-subject variations of circadian pattern in Cyp3a11 40 . We show Bmal1 controls circadian expressions of Cyp3a11 in the present study and of intestinal Mrp2 in our recent study 41 . BMAL1 has potential to regulate other key metabolic enzymes and transporters such as UGT1A1, CES2 and P-gp 42 .…”
Section: Discussionsupporting
confidence: 80%
“…Diurnal expression of some types of ABC transporters are regulated by the molecular circadian clock 10 , 11 , 13 . Gene products of Clock and Bmal1 form a heterodimer that activates the transcription of Period ( Per ) and Cryptochrome ( Cry ) genes through E-box (CACGTG) or E-box-like (CACGTT) enhancer sequences 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several types of ABC transporters also function in the biliary, intestinal, and renal elimination of drugs 9 . The expression and function of some ABC transporters, such as P-glycoprotein (P-gp), multidrug resistance-associated protein 2 (MRP2), and breast cancer-resistant protein (BCRP), exhibit diurnal variation, resulting in dosing time-dependent differences in drug disposition 10 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that molecular components of the circadian clock can regulate the time‐dependent expression of the Gp2 gene, a key regulator in intestinal immunity, in mouse Peyer's patches through the activation of CREB. Previous studies demonstrated circadian expression of intestinal cell‐surface proteins, such as xenobiotic efflux transporter (e.g., Mdr1, Bcrp and Mrp2), and their expression rhythm was also controlled by a molecular clock (Hamdan et al, 2012; Murakami, Higashi, Matsunaga, Koyanagi, & Ohdo, 2008; Yu et al, 2019). The expression of some such transporters increases from the late light phase to the early dark phase, during which nocturnal active rodents wake up and start daily food intake.…”
Section: Discussionmentioning
confidence: 99%